Variational Principles and Their Applications (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
There are many variational calculations of energies of various systems which have applications in Rydberg states and polarizabilities of these systems. There are variational calculations of scattering functions which have applications in calculations of excitation, photoabsorption, and radiative attachment cross sections. A few of these applications are mentioned.
Keywords: Variational principles; Variational calculations; Ritz variational method; Rydberg states; Photoionization; Electron-hydrogen scattering; Positron-hydrogen scattering